Method for preparing lithium battery negative electrode material by microwave-assisted recovery of modified waste graphite and prepared modified graphite lithium battery negative electrode material

Through microwave-assisted recycling of modified waste graphite and forming composite materials with asphalt, the problems of large solvent consumption, complex process and poor performance when recycling graphite materials in the prior art are solved, efficient and environmentally friendly graphite material recycling and regeneration modification are achieved, and high-performance lithium battery negative electrode materials are obtained.

CN119674036APending Publication Date: 2025-03-21KAIFENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411944777.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art has problems such as large organic solvent consumption, complex process routes, poor electrolyte compatibility and poor cycle stability when recycling and reuse of waste lithium battery graphite anode materials.

Method used

The microwave-assisted recycling of modified waste graphite is used to separate the graphite from impurities through ultrasonic treatment and microwave treatment, and then mixed with asphalt in proportion for ball milling to form asphalt/graphite composite material, and a core-shell-like composite material is formed by a sectioned heating solid-phase pyrolysis process.

Benefits of technology

The efficient recycling and regeneration modification of the graphite anode material of waste lithium battery is realized. The modified graphite material obtained has high specific capacity, good cycle stability and low production cost, and is suitable for lithium-ion battery anode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674036A_ABST
    Figure CN119674036A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery negative electrode material recovery, and particularly relates to a method for preparing a lithium battery negative electrode material through microwave-assisted recovery of modified waste graphite and the prepared modified graphite lithium battery negative electrode material. Aiming at the problems of poor electrolyte compatibility, poor cycling stability and the like of a graphite material, asphalt is adopted as a carbon source, recycled graphite is subjected to coating modification, and then a segmented heating solid-phase pyrolysis process is performed to prepare the graphite-based composite material with the core-shell-like structure. The waste graphite recycling, modifying and regenerating process disclosed by the invention has the characteristics of simplicity, high efficiency and environmental protection, the recycled graphite can be directly used as a lithium battery negative electrode material after being regenerated and modified, and the waste graphite recycling, modifying and regenerating process has the advantages of low cost, high reversible specific capacity and good cycle performance; and a new technical route is provided for preparation of a high-performance and low-cost lithium ion battery negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery negative electrode material recovery, and in particular relates to a method for preparing lithium battery negative electrode materials by microwave-assisted recovery of modified waste graphite and the prepared modified graphite lithium battery negative electrode materials. Background Art

[0002] Lithium-ion batteries (LIBs) have been rapidly developed due to their high specific energy, good cycle performance, and no memory effect. They are widely used in electronic products, transportation, military, aerospace and other fields.

[0003] As the main negative electrode material for commercial lithium-ion batteries, graphite is the key to reducing the production cost and improving the performance of lithium batteries, and its usage is also increasing year by year. However, due to factors such as the cost of raw materials and energy in the graphitization process, the price of high-performance artificial graphite has been rising year by year, and natural graphite has been listed as a supply risk material worldwide, and its mining and export are restricted. The contradiction between the demand and supply of the graphite negative electrode market has become increasingly prominent, and the search for low-cost graphite material supply channels has received widespread attention in the lithium-ion battery industry. In the preparation process of ultra-high power graphite electrodes, nearly 150,000 tons of graphite waste will be generated each year, plus the 20,000 to 100,000 tons of recycled waste graphite generated each year by lithium battery recycling, the output is amazing. If these waste materials can be recycled and developed and re-prepared into negative electrode graphite materials for lithium-ion batteries, it will have huge economic and practical benefits.

[0004] The recycling and reuse of waste graphite is an effective way to alleviate the increase in graphite demand, reduce battery production costs and reduce environmental pollution. These waste graphite raw materials have the advantages of low cost and wide sources, and retain the layered structure. After recycling, they can be reused in the fields of energy storage, water treatment and preparation of graphene precursors. However, waste graphite is doped with impurities and has problems such as structural cracks, so it cannot be directly used as a lithium battery electrode material. At present, most of the research reports on the recycling of waste graphite use strong acids, strong alkalis or ultra-high temperatures to treat graphite. The use of a large amount of solvents is likely to cause environmental pollution, which is not conducive to large-scale industrial production and application. At the same time, the graphite negative electrode itself has poor electrolyte compatibility and high volume expansion rate when in use. In order to improve the comprehensive performance of battery negative electrode materials, it is necessary to regenerate and modify the waste graphite after recycling to effectively improve the electrochemical performance of graphite negative electrode materials.

[0005] In summary, the current recycling and resource utilization of graphite negative electrode materials in waste lithium batteries often have problems such as large organic solvent consumption and complex process routes. At the same time, in view of the poor electrolyte compatibility and poor cycle stability of graphite materials at this stage, the present invention proposes a new method for recycling and functional modification of graphite negative electrodes of waste lithium-ion batteries to better solve the above technical problems. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing low-cost, high-performance lithium battery negative electrode materials based on microwave-assisted recovery and modification of waste graphite. The green recovery of waste lithium battery graphite negative electrode materials is realized by microwave assistance, and the process is simple and does not require organic solvents. At the same time, in view of the problems of poor cycle performance and low specific capacity of graphite when used as negative electrode material, the recycled graphite is functionalized and regenerated.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing lithium battery negative electrode materials by microwave-assisted recycling and modification of waste graphite comprises the following steps: S1. Discharge and disassemble the waste lithium battery to obtain the graphite negative electrode sheet, cut it into small pieces, add deionized water to disperse it, and then ultrasonically treat it for 5-30 minutes to separate the graphite material from the copper foil, and filter it to obtain the graphite dispersion; S2. placing the graphite dispersion obtained in step S1 in a microwave reactor and subjecting it to microwave treatment for 5-10 minutes under stirring conditions, cooling it to room temperature, filtering, washing and drying it to obtain recovered graphite, wherein the microwave treatment causes impurities such as a binder (CMC) and an organic lithium salt to be immersed in the aqueous solution and separated from the graphite, and by regulating the power and reaction time of the microwave reactor, the impurities can be dissolved more thoroughly and the ion leaching efficiency can be improved; S3. The recycled graphite obtained in step S2 and asphalt are added to a ball mill in a mass ratio of 100:5-20, a protective agent is added after adjusting the ball-to-material ratio, the ball mill is placed on a planetary ball mill, and the mixture is ball-milled at a speed of 100-500 r / min for 1-8 h to coat the surface of the waste graphite with a layer of asphalt to obtain an asphalt / graphite composite material; S4. The asphalt / graphite composite material obtained in step S3 is placed in a vacuum drying oven to dry and remove the solvent to obtain an asphalt / graphite composite solid powder material, which is then ground and classified to obtain an asphalt / graphite composite solid powder material; S5. The solid powder material obtained in step S4 is placed in a tubular furnace, and after a staged heating solid phase pyrolysis process, cooling, and grinding, a core-shell structure graphite-based composite material is obtained. The pyrolysis carbon coating of organic matter is achieved by staged heating. The temperature of the first stage is 300-600°C, and the insulation time is 1-2 h. This stage is mainly the asphalt decomposition process. At the same time, the untreated organic matter in the waste graphite is decomposed to generate small molecules. The temperature of the first stage is 300-600°C, and the insulation time is 1-2 h; the temperature of the second stage is 600-900°C, and the insulation time is 2-6 h. This stage mainly involves the carbonization of organic matter such as asphalt to form amorphous carbon, which is deposited and coated on the graphite surface. The temperature of the third stage is 900-1200℃, and the insulation time is 1-2h. In this stage, the amorphous carbon formed by the pyrolysis of organic matter such as asphalt further combines with the graphite surface and enters into the pores of the graphite crystal to form a graphite composite material with a core-shell structure. The coated carbon layer can effectively improve the crystal defects on the graphite surface and increase the material's tap density.

[0008] Furthermore, the waste graphite material in step S1 includes negative electrode graphite sheets from dismantled retired lithium batteries and graphite scraps generated during electrode cutting.

[0009] Furthermore, in step S3, the power of the microwave reactor is 200-800W; the pellet-to-material ratio (mass ratio) is (10-100):1; the solvent is one of methanol, ethanol, and tetrahydrofuran, and the added amount is 5-20 mL.

[0010] Furthermore, in step S4, the drying temperature is 80-120° C. and the drying time is 8-24 hours; the grinding is performed by mechanical ball milling or mortar grinding.

[0011] Furthermore, in the step S5, the solid-phase pyrolysis process of stepwise heating is protected by inert gas.

[0012] Another object of the present invention is to provide a modified graphite lithium battery negative electrode material prepared by the above method. The method of the present invention is used to realize the recovery and regeneration of waste graphite negative electrode materials. The regenerated and modified graphite composite material can be directly used as a negative electrode material for lithium ion batteries.

[0013] Mechanism: The present invention uses asphalt as a coating modification material, and realizes the coating modification of recycled graphite through mechanical ball milling and solid-phase pyrolysis carbonization process. Asphalt is a carbon source, and a layer of carbon material is deposited on the surface of the recycled graphite after solid-phase pyrolysis, which can repair the defects on the surface of the graphite structure (such as voids, cracks, etc.), improve the tap density of the material, and obtain a graphite-based composite material with a core-shell structure. The maximum specific capacity of the material after recycling and modification is 359.2 mAh / g, and the capacity is 357.4 mAh / g after 100 cycles, reaching commercial level. The composite material can be directly used as a negative electrode material for lithium-ion batteries, and has the advantages of low cost, good cycle performance, and high specific capacity.

[0014] The present invention has the advantages that: 1. The present invention provides a green method for recycling and regenerating graphite negative electrodes in waste lithium-ion batteries. Through microwave-ultrasound assisted treatment, ultrasound causes graphite on copper foil to be peeled off and dispersed in an aqueous solution. By regulating the power and reaction time of the microwave reactor, impurities can be dissolved more thoroughly and the ion leaching efficiency can be improved, thereby achieving efficient recycling of waste graphite. It does not require a large amount of organic solvents, has the characteristics of energy conservation and environmental protection, and has wide applicability. It is suitable for the recycling and resource utilization of negative electrode graphite sheets from dismantling retired lithium batteries and graphite scraps generated during electrode cutting; 2. The present invention uses recycled graphite as raw material and provides a method for preparing a low-cost, high-performance lithium battery negative electrode material. Low-cost asphalt is used as a coating modifier. A layer of asphalt is coated on the surface of the recycled graphite through a simple mechanical ball milling process, and then a dense carbon layer structure is formed on the surface of the waste graphite through a high-temperature carbonization process, which effectively improves the lithium ion migration rate and the specific capacity of the negative electrode material; 3. The present invention realizes the recycling and cyclic utilization of waste graphite negative electrode materials. The preparation process adopted is simple and easy. After coating and modification, the material tap density can be effectively improved. The obtained graphite-based composite material can be directly used as a lithium battery negative electrode material, and has the advantages of high specific capacity and good cycle performance; 4. The method of the present invention can realize the recovery and regeneration of waste graphite negative electrodes, providing a new idea for the resource utilization of waste graphite. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 These are scanning electron microscope photographs of the recycled graphite in Example 1 before (a) and after (b) asphalt coating treatment.

[0016] Figure 2 This is the XRD pattern of the regenerated modified graphite composite material prepared in Example 1.

[0017] Figure 3The graphite composite material obtained in Example 1 is used as the negative electrode material of a lithium battery, and the charge and discharge curves of the assembled lithium-ion battery are obtained by conducting an electrochemical performance test.

[0018] Figure 4 The graph of cycle stability obtained by using the graphite composite material obtained in Example 1 as a negative electrode material for a lithium battery and conducting an electrochemical performance test on an assembled lithium-ion battery. DETAILED DESCRIPTION

[0019] Example 1 A method for preparing lithium battery negative electrode materials based on microwave-assisted recovery and modification of waste graphite comprises the following steps: S1. Discharge and disassemble the waste lithium battery to obtain the graphite negative electrode sheet, cut it into small pieces, add deionized water to disperse it, and then ultrasonically treat it for 10 minutes to separate the graphite material from the copper foil. Filter it to obtain the graphite dispersion; S2. The graphite dispersion obtained in S1 is placed in a microwave reactor for microwave treatment, the stirrer in the microwave reactor is turned on, and the mixture is stirred for 15 minutes to separate the impurities such as the binder and the organic lithium salt from the graphite by immersing them in the aqueous solution, and the graphite is fully dispersed in the suspension. The microwave power is adjusted to 800 W, and the mixture is cooled to room temperature after reacting for 8 minutes, and the recovered graphite material is obtained after filtering, washing, and drying; S3. Weigh 100 g of recycled graphite and 10 g of asphalt and add them to a ball mill, adjust the ball-to-material ratio (mass ratio) to 50:1, add 10 mL of ethanol solvent as a protective agent, place the ball mill on a planetary ball mill, and perform mechanical ball milling and mixing at a speed of 200 rpm for 2 hours, and coat a layer of asphalt on the surface of the graphite waste to obtain an asphalt / graphite composite material, wherein the asphalt is one of petroleum asphalt and coal asphalt; S4. The graphite / asphalt composite material obtained in step S3 is placed in a vacuum drying oven and dried at 80° C. for 12 h to remove the solvent to obtain an asphalt / graphite composite solid powder material; S5. Grind and classify the solid material obtained in step S4 to obtain a asphalt-coated graphite solid powder material; S6. The solid powder material obtained in step S5 is placed in a tubular furnace, and segmented heating is used to realize the pyrolysis of organic matter and carbon-coated modified graphite. The temperature of the first stage is set at 300°C and the insulation time is 1h; the temperature of the second stage is set at 650°C and the insulation time is 3h; the temperature of the third stage is set at 900°C and the insulation time is 2h. After cooling and grinding, a graphite composite material is obtained. The segmented heating pyrolysis can avoid the rapid melting of asphalt during the rapid carbonization process, resulting in uneven reaction and agglomeration; in addition, it can effectively prevent the small molecules produced by the decomposition of asphalt from overflowing too fast, and the coated carbon layer produces too large gaps, resulting in a decrease in the material tap density and affecting the electrochemical performance. The performance parameters and electrochemical test results of the prepared asphalt carbon-coated modified recycled graphite are shown in Table 1. It can be seen from Table 1 that after the asphalt coating modification by the method of the present invention, the tap density of the recycled graphite is significantly increased and the specific surface area is reduced. This is because after the asphalt is carbonized at high temperature, the carbon layer coated on the graphite surface improves the morphology of the graphite surface, repairs the defects on the surface of the graphite structure (such as voids, cracks, etc.), and makes the contact between the material particles better, thereby increasing the tap density of the material, improving the electrochemical properties of the material, and showing higher specific capacity and cycle stability.

[0020] Example 2 The difference between Example 2 and Example 1 is that the ultrasonic treatment time is 5min, the power of the microwave reactor is 200W, the microwave treatment time is 5min, the ratio of asphalt to recycled graphite is 5:100 by mass; the ball-to-material ratio (mass ratio) is 10:1; the solvent added is 5 mL of methanol, the speed of the planetary ball mill is 100 r / min, and the ball milling mixing time is 1h; the drying temperature is 120°C for 8h; the temperature of the first stage in the staged heating solid phase pyrolysis process is set at 600°C for 2h; the temperature of the second stage is set at 600°C for 4h, and the temperature of the third stage is set at 1200°C for 1h; the performance parameters and electrochemical test results of the prepared asphalt carbon coated modified recycled graphite are shown in Table 1. Compared with Example 2, Example 1 shows higher initial performance and better cycle stability, which is because more active sites are exposed after the waste graphite is regenerated and modified, resulting in higher battery capacity. When the microwave energy is low, the microwave treatment process is not sufficient, the impurities in the graphite layer are not completely removed, the prepared material has a low tap density, and exhibits low capacity and cycle stability. This shows that microwave treatment can achieve the purpose of efficiently recycling waste graphite.

[0021] Example 3 The difference between Example 3 and Example 1 is that the ultrasonic treatment time is 30min, the power of the microwave reactor is 600W, the microwave treatment time is 10min, the ratio of asphalt to recycled graphite is 20:100 by mass; the ball-to-material ratio (mass ratio) is 100:1; the solvent added is 20 mL tetrahydrofuran, the speed of the planetary ball mill is 500 r / min, and the ball milling mixing time is 8h; the drying temperature is 100℃ for 24h; the temperature of the first stage in the staged heating solid phase pyrolysis process is set at 400℃ and the insulation time is 1.5h; the temperature of the second stage is set at 900℃ and the insulation time is 6h, and the temperature of the third stage is set at 1000℃ and the insulation time is 1.5h; the performance parameters and electrochemical test results of the prepared asphalt carbon-coated modified recycled graphite are shown in Table 1. Compared with Example 1, as the asphalt content increases, a thicker carbon layer is deposited on the surface of the recycled graphite, which is not conducive to the subsequent penetration of the electrolyte, nor is it conducive to the insertion and extraction of lithium ions, resulting in a decrease in the capacity of the material.

[0022] Example 4 The difference between Example 4 and Example 1 is that after the recycled graphite is obtained by microwave treatment, it is not coated with asphalt, and the recycled graphite is directly used as the negative electrode material of the lithium battery, button batteries are assembled, and electrochemical performance tests are performed. Comparing Example 4 with Examples 1-3, when the recycled graphite that has not been modified by asphalt coating is directly used as the negative electrode material of the lithium battery, the structural defects of the graphite are not repaired, the initial charge and discharge capacity is too low, and the cycle stability is poor. It cannot be directly used as the negative electrode material of the battery, and the recycled graphite needs to be regenerated and modified.

[0023] Electrochemical performance test The graphite composite materials prepared in Examples 1-4 of the present invention were respectively used as lithium battery negative electrode materials, mixed with conductive graphite and PVDF in a ratio of 8:1:1, and lithium sheets were used as counter electrodes. 2032 button-type lithium batteries were assembled in a high-purity argon inert glove box, and electrochemical performance tests were performed at a charge and discharge rate of 0.5C. The test results are listed in Table 1.

[0024] like Figure 1 As shown in the figure, the structure of the recycled waste graphite is irregular and flake-like, with many defects such as cracks and grooves on the surface. After asphalt modification, an obvious coating layer can be observed on the graphite surface, indicating that the asphalt deposits a layer of amorphous carbon on the graphite surface during the carbonization process. The graphite structure is more regular than the raw material, and the groove-like defects on the surface are significantly reduced, showing a spherical structure after coating. This is because the asphalt will fill in the grooves during the high-temperature melting process, and fill the defective parts after carbonization, so as to achieve fine-tuning of the graphite surface structure.

[0025] from Figure 2It can be seen that the XRD diffraction peaks of the coated material are basically the same as the standard peaks of graphite. The diffraction peak of the material at 26.5° corresponds to the (002) crystal plane, and the diffraction peak at 54.6° corresponds to the (004) crystal plane, indicating that asphalt coating will not destroy the crystal structure of graphite.

[0026] Figure 3 This is the charge and discharge curve of the button cell assembled with the graphite electrode material in Example 1 after 100 cycles at a current of 0.5C. It can be seen from the figure that as the cycle proceeds, the material discharges steadily, the specific capacity does not change much, and the discharge platform is obvious. Figure 4 The cycle stability curve of the graphite electrode material under 0.5C charge and discharge conditions shows that the initial specific capacity is 240.6 mAh / g, the maximum specific capacity is 359.2 mAh / g, and the capacity is 352.8 mAh / g after 100 cycles. The slight attenuation in the first 20 cycles is attributed to the insufficient wettability between the surface of the electrode material and the front of the electrolyte. When lithium ions are embedded in the active material, they are not completely diffused into the active material. The subsequent specific capacity gradually increases and tends to be stable with the increase in the number of cycles. After 200 cycles, it remains at about 350 mAh / g. This shows that the graphite material modified and recovered by the method of the present invention exhibits good cycle stability when used as a negative electrode material for lithium batteries.

Claims

1. A method for preparing lithium battery negative electrode materials by microwave-assisted recovery and modification of waste graphite, characterized in that: The following steps are involved: S1. Discharge and disassemble the waste lithium battery to obtain the graphite negative electrode sheet, cut it into small pieces, add deionized water to disperse it, then ultrasonically treat it for 5-30 min, and filter it to obtain the graphite dispersion; S2. The graphite dispersion obtained in step S1 is placed in a microwave reactor and subjected to microwave treatment for 5-10 min under stirring conditions, then cooled to room temperature, filtered, washed, and dried to obtain recovered graphite; S3. The recovered graphite and asphalt obtained in step S2 are added to a ball mill in a mass ratio of 100:5-20, a protective agent is added after adjusting the ball-to-material ratio, the ball mill is placed on a planetary ball mill, and the mixture is ball-milled at a speed of 100-500 r / min for 1-8 h to obtain an asphalt / graphite composite material; S4. The asphalt / graphite composite material obtained in step S3 is placed in a vacuum drying oven to dry and remove the solvent to obtain an asphalt / graphite composite solid powder material, which is then ground and classified to obtain an asphalt / graphite composite solid powder material; S5. The solid powder material obtained in step S4 is placed in a tubular furnace, and after a staged heating solid-phase pyrolysis process, cooling, and grinding, a core-shell structured graphite-based composite material is obtained, wherein the staged heating solid-phase pyrolysis process includes a first stage temperature of 300-600°C and a heat preservation time of 1-2 h; a second stage temperature of 600-900°C and a heat preservation time of 2-6 h; a third stage temperature of 900-1200°C and a heat preservation time of 1-2 h.

2. The method for preparing a lithium battery negative electrode material by microwave-assisted recovery and modification of waste graphite as claimed in claim 1, characterized in that: The waste graphite materials in step S1 include negative electrode graphite sheets from dismantled retired lithium batteries and graphite scraps generated during electrode cutting.

3. The method for preparing a lithium battery negative electrode material by microwave-assisted recovery and modification of waste graphite as claimed in claim 1, characterized in that: The power of the microwave reactor in step S3 is 200-800W; the solvent is one of methanol, ethanol and tetrahydrofuran, and the added amount is 5-20 mL.

4. The method for preparing a lithium battery negative electrode material by microwave-assisted recovery and modification of waste graphite as claimed in claim 1, characterized in that: In the step S4, the drying temperature is 80-120° C. and the drying time is 8-24 hours; the grinding is performed by mechanical ball milling or mortar grinding.

5. The method for preparing lithium battery negative electrode material by microwave-assisted recovery and modification of waste graphite as claimed in claim 1, characterized in that: The stepwise heating solid phase pyrolysis process in step S5 is protected by inert gas.

6. A modified graphite lithium battery negative electrode material prepared by the method according to any one of claims 1 to 5.